Mineralocorticoid Receptor in Smooth Muscle Contributes to Pressure Overload–Induced Heart Failure. (February 2021) - Kim, Seung Kyum; Biwer, Lauren A.; Moss, M. Elizabeth; Man, Joshua J.; Aronovitz, Mark J.; Martin, Gregory L.; Carrillo-Salinas, Francisco J.; Salvador, Ane M.; Alcaide, Pilar; Jaffe, Iris Z.
Abstract : Background: Mineralocorticoid receptor (MR) antagonists decrease heart failure (HF) hospitalization and mortality, but the mechanisms are unknown. Preclinical studies reveal that the benefits on cardiac remodeling and dysfunction are not completely explained by inhibition of MR in cardiomyocytes, fibroblasts, or endothelial cells. The role of MR in smooth muscle cells (SMCs) in HF has never been explored. Methods: Male mice with inducible deletion of MR from SMCs (SMC-MR-knockout) and their MR-intact littermates were exposed to HF induced by 27-gauge transverse aortic constriction versus sham surgery. HF phenotypes and mechanisms were measured 4 weeks later using cardiac ultrasound, intracardiac pressure measurements, exercise testing, histology, cardiac gene expression, and leukocyte flow cytometry. Results: Deletion of MR from SMC attenuated transverse aortic constriction-induced HF with statistically significant improvements in ejection fraction, cardiac stiffness, chamber dimensions, intracardiac pressure, pulmonary edema, and exercise capacity. Mechanistically, SMC-MR-knockout protected from adverse cardiac remodeling as evidenced by decreased cardiomyocyte hypertrophy and fetal gene expression, interstitial and perivascular fibrosis, and inflammatory and fibrotic gene expression. Exposure to pressure overload resulted in a statistically significant decline in cardiac capillary density and coronary flow reserve in MR-intact mice. These vascular parameters were improved in SMC-MR-knockout mice compared with MR-intact littermates exposed to transverse aortic constriction. Conclusions: These results provide a novel paradigm by which MR inhibition may be beneficial in HF by blocking MR in SMC, thereby improving cardiac blood supply in the setting of pressure overload–induced hypertrophy, which in turn mitigates the adverse cardiac remodeling that contributes to HF progression and symptoms. Abstract : Supplemental Digital Content is available in the text.